Prophet Muhammad the night journey - Khan,saniyasnain (UAE goodwordbooks, 2024)
The book "Tell Me About the Prophet Muhammad" by Saniyasnain Khan summarizes the Night Journey (Isra and Miraj) as part of Prophet Muhammad's life story. The narrative describes Muhammad's miraculous journey from Mecca to Jerusalem (Isra) and then his ascension to the heavens (Miraj). This event is presented as a significant miracle, where the Prophet's heart was purified, he traveled on al-Buraq, and led other prophets in prayer before ascending to meet with Allah. The book also highlights the spiritual lessons derived from this event, emphasizing the importance of faith and divine connection
This book is from Islamic stories shelf:C R:1